OPTIMALISASI PENGGUNAAN INSTAGRAM SEBAGAI UPAYA UMKM NAIK KELAS Di DESA KUBANG JAYA - Sidoretno, Wahyu Margi; Wardaniati, Isna; Pratiwi, Yuharika; Lestari, Suci Shinta (LPPM Institut Pendidikan Nusantara Global, 2022)
Usaha Mikro Kecil dan Menengah (UMKM) has recently become a trend in the field of entrepreneurship. It becomes a business choice for beginners. The variety of product types in UMKM increases the competition. Minimum stock and medium facilities become the obstacles in developing their business. Social media such as Instagram (IG) can be used as alternative media promotion due to their accessibility and low cost. This community services activity aims to educate the UMKMs in the village of Kubang Jaya about the use of social media Instagram as promotion product media. In addition, this activity also conducts training in taking product photos to increase the selling price. This activity uses a contextual approach method such as; a theoretical class and workshop. The participants can directly update their photo products on their own Instagram. The results of this activity were their understanding the Instagram as a marketing media.